ANALISIS PENERAPAN AKUNTANSI LINGKUNGAN PADA RSU IMELDA PEKERJA INDONESIA - Aurelya Zai, Cindy Tania; Hutapea, Herti Diana; Gaol, Vebry M. Lumban (Jurnal Akuntansi Kompetif, 2025)
This study aims to analyze the application of environmental accounting, especially in the aspects of: recognition, measurement, and presentation of environmental costs in financial statements at the Imelda Buruh Indonesia General Hospital. The research method used in this study is descriptive qualitative, with data sources obtained from primary data and secondary data. The results of this study indicate that in the aspect of environmental cost recognition, it is generally recorded in the operational expense item and its details have not been presented separately in the income statement. In the aspect of measurement, environmental costs are measured using monetary units by referring to budget realization based on the amount of money spent at the time the transaction occurs. And in the aspect of environmental cost presentation, environmental costs are not presented separately in the financial statements, but are combined in other general accounts such as operational expenses, maintenance expenses, and cleaning expenses. This causes environmental costs not to be seen explicitly in the financial statements. Keywords: Environmental Accounting, Hospitals, and Accounting Treatment.